REAKSI PELAKU EKONOMI TERHADAP KEBIJAKAN NEW NORMAL DI KOTA PEKANBARU TAHUN 2020 - Henny Saputri; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Covid-19 Pandemic that entered Indonesian was designated as a non-natural disaster that was being watched out for since March 2020. This pandemic has caused various impact in various sector, both the health, economic and social sectors. The central and regional government have issued various policies to control the increase in cases affected by Covid-19. The Government is also trying to control economic stability by implementing a New Normal policy, but after the implementation of New Normal policy, Covid-19 cases are increasing.The purpose of this study is to find out how economic actors react to the New Normal policy in Pekanbaru in 2020. This study uses a qualitative approach with descriptive method. In collecting data the author uses interview and documentation techniques.The New Normal policy caused a reaction from the government, business actors and the community. It’s because in the establishment of the New Normal policy there are conflicting interest, namely between economic interest and health interest. Each actors has different interest both the government and business actors or the community. Due to different interest in the midst the Covid prevention policies, there will be a reaction. From this research, it can be seen the various reactions made by the government, business actor and the community. That is seen by criticizing and protesting directly to the government or accepting and obeying the New Normal policy. The reaction of economic actors to the New Normal policy include being able to accept it while still providing some suggestions, accept without protesting, and there are also those who ignore the New Normal Policy. Keyword : New Normal Policy, Reaction